Pengaruh Budaya organisasi, Kompetensi dan Pengembangan Karir Terhadap Produktivitas Kerja Karyawan Pada PT. Pos Indonesia (Persero) Cabang Kabupaten Sumenep - Banowati, Berliana Tri; Susyanti, Jeni; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to determine the partial influence between organizational culture, competence and career development on employee work productivity. This type of research uses a quantitative approach. The population that is the focus is employees of PT Pos Indonesia (Persero) Sumenep Regency Branch. A total of 93 employees were selected as samples with purposive sampling techniques. Data collection was carried out through questionnaires and analyzed through the Statistical Program Social Science (SPSS). The results of the study show that Organizational Culture, Competence and Career Development have a partial effect on Employee Work Productivity. Keywords: Organizational Culture, Competence, Career Development, Employee Work Productivity